2007
DOI: 10.1038/sj.leu.2404577
|View full text |Cite
|
Sign up to set email alerts
|

Acute lymphoblastic leukemia with t(4;11) in children 1 year and older: The ‘big sister’ of the infant disease?

Abstract: The t(4;11)-positive acute lymphoblastic leukemia (ALL) is a rare disease in children above the age of 1 year. We studied the clinical and biological characteristics in 32 consecutively diagnosed childhood cases (median age 10.0 years, range 1.0-17.1 years). Immunophenotyping revealed a pro-B and a pre-B stage in 24 and eight cases, respectively. IGH genes were rearranged in 84% of leukemias with a predominance of incomplete DJ H joints. Whereas IGK-Kde and TCRD rearrangements were rare, TCRG rearrangements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…[17][18][19][20] We therefore determined the IGH rearrangements in 130 children with HeH BCP ALL (90 consecutively recruited and 40 selected cases) and correlated their individual sequence and clonality pattern with their respective IGH allele and/or chromosome 14 copy numbers. Our aim was to determine to which extent these IGH rearrangement patterns may be used to delineate monoclonal cases with a trisomy 14 from oligoclonal ones with a disomy 14 and to discuss the implications of our findings for leukemia biology and MRD analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] We therefore determined the IGH rearrangements in 130 children with HeH BCP ALL (90 consecutively recruited and 40 selected cases) and correlated their individual sequence and clonality pattern with their respective IGH allele and/or chromosome 14 copy numbers. Our aim was to determine to which extent these IGH rearrangement patterns may be used to delineate monoclonal cases with a trisomy 14 from oligoclonal ones with a disomy 14 and to discuss the implications of our findings for leukemia biology and MRD analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In an early study of childhood t(4;11)-positive ALL, we observed that treatment outcome differed by age group with infants having the worst outcome, 5 a finding that has since been confirmed by many other studies including one published in this issue of Leukemia. [6][7][8] Despite recent improvements in the overall treatment outcome for ALL patients, MLL-AF4 fusion is still associated with a dismal prognosis in infants (especially those younger than 6 months ) and adults. 4,[6][7][8] Of note, a difference in outcome by age has also been observed in cases with the t(9;22)(q34;q11.2) and BCR-ABL fusion.…”
mentioning
confidence: 99%
“…[6][7][8] Despite recent improvements in the overall treatment outcome for ALL patients, MLL-AF4 fusion is still associated with a dismal prognosis in infants (especially those younger than 6 months ) and adults. 4,[6][7][8] Of note, a difference in outcome by age has also been observed in cases with the t(9;22)(q34;q11.2) and BCR-ABL fusion. 9 The underlying basis of age differences in outcome among leukemias with the same primary genetic abnormality remains unknown, but has been the subject of many investigations that raise several intriguing hypotheses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 With respect to clinical course and biological features, infant leukemia exhibits different characteristics to a phenotypically and cytogenetically similar disease in older age. 3,4 A high rate of breakpoints located in the telomeric portion of the MLL breakpoint cluster region (BCR), similar to therapyinduced acute leukemia associated with topoisomerase II inhibitors, suggested a similar mechanism for MLL rearrangement generation in infant leukemia. Other DNA features, such as scaffold-attachment regions (SAR), DNAse I hypersensitivity sites and initiation sites of apoptotic nucleases, have been discussed to be involved in alternative break mechanisms.…”
mentioning
confidence: 99%